Heroes of World War II : 50 inspiring stories of bravery : a World War II book for kids - Halls, Kelly Milner, 1957- (Rockridge Press, 2021)
Profiles fifty heroes of World War II, and explores their impact on the war. Includes color illustrations and additional resources.